2018
DOI: 10.14406/acu.2018.002
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Proper Treatment Time of Electronic Moxibustion - Focusing on the Skin Safety -

Abstract: 동국대학교 한의과대학 원전의사학교실, 4 동제메디칼Objectives : Electronic moxibustion was developed to overcome the weakness of conventional moxibution. However, in spite of many benefits, it also can not be entirely free from the concern of burning. This study was performed to investigate the proper treatment time of electronic moxibustion. Methods : Male sprague-Dawley rats weighing about 350 g were used. Animals were anesthetized with sodium pentobarbital and shaved on the abdomen or back. The full charged-electronic moxibustio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…The relationship between moxibustion temperature and burns has been widely researched to determine safety. In an vivo model, burns occurred on the skin of the back of the rat in 4 minutes when electronic moxibustion was performed at 47°C, and burn occurred within 1 minute when the device was set at 49°C [15]. Another study reported that if the temperature of electronic moxibustion was rapidly increased to its maximum within 1 minute, erythema may persist at the application site beyond 24 hours [7].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between moxibustion temperature and burns has been widely researched to determine safety. In an vivo model, burns occurred on the skin of the back of the rat in 4 minutes when electronic moxibustion was performed at 47°C, and burn occurred within 1 minute when the device was set at 49°C [15]. Another study reported that if the temperature of electronic moxibustion was rapidly increased to its maximum within 1 minute, erythema may persist at the application site beyond 24 hours [7].…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey on the clinical use of moxibustion, 91% of Korean medicine doctors were applying moxibustion, with the most common type being the adhesive-type indirect moxibustion using traditional moxa [6]. EM was recently developed to minimize side effects such as burns and overcome therapeutic complications such as smoke or smell arising from TIM [11]. Furthermore, there have been clinical studies investigating the efficacy of EM for breast cancer-related lymphedema [16], ankylosing spondylitis [17], shoulder periarthritis [12], knee osteoarthritis [18,19], lumbar stenosis [20] and traffic accident-induced lumbago [10].…”
Section: Discussionmentioning
confidence: 99%
“…Chae et al [13] reported no significant difference in body surface temperature after applying traditional moxibustion or EM for 2 minutes. Park et al [11] reported on the proper treatment duration based on skin safety to prevent side effects by utilizing EM on the abdominal and back skin of rats. Furthermore, to substitute the thermal stimulation effect of traditional moxibustion, it is important to maintain heat conductance in deep skin tissues [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations